anonymous
  • anonymous
Find an equation of a line parallel to the line 3x-2y=4 and containing the point (3,-5)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
\[2y=4\]is this wat u tryin to find
anonymous
  • anonymous
yes
anonymous
  • anonymous
parallel = means the same slope re-write your ew as: 2y=3x-4 or y=3/2 x -2 so, slope your existing line is: m=3/2 so, eq of parallel through the point (3,5): y-5=3/2 *(x-3) y=3/2x -9/2 +5=3/2 x+1/2

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
That makes sense.... Thank you!
anonymous
  • anonymous
Can you help me with another one?
anonymous
  • anonymous
shoot... I need to go soon
anonymous
  • anonymous
Its like the one you just helped me with only perpendicular to the line 3x-2y=4 and containing points 3,-5
anonymous
  • anonymous
try to do it yourself - I'll help. just remember that perpendicular means that your line will have slope (m2) = -1/m1... so, if re-write your eq: y=3/2 x -2 so, for perp line: m2=-2/3 eq of the line: y-(-5)=-2/3 (x-3) simplify, please
anonymous
  • anonymous
So then y=-2/3x+6/3-5?
anonymous
  • anonymous
y+5=-2/3 *x +2 y=-2/3 *x -3
anonymous
  • anonymous
do you see it?
anonymous
  • anonymous
So the equation is y=-2/3x-3?
anonymous
  • anonymous
yep... to be exact: y=(-2x/3 ) -3
anonymous
  • anonymous
Okay, I guess I just don't get how you suddenly got to x+2 in the end
anonymous
  • anonymous
let's go back to: y-(-5)=-2/3 (x-3) i think that the way it written it could be confusing... let's try differently: y+5= x* (-2/3) -3* (-2/3) y+5=-2x/3 +2 (-3 in numerator & -3 in dominator are canceled out) is it better...?
anonymous
  • anonymous
That does make better sense. Math is like a whole other language for me, lol. Thank you so much for your help
anonymous
  • anonymous
Great! Welcome :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.